The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1038/s41598-021-81454-7
|View full text |Cite
|
Sign up to set email alerts
|

The role of dorsolateral and ventromedial prefrontal cortex in the processing of emotional dimensions

Abstract: The ventromedial and dorsolateral prefrontal cortex are two major prefrontal regions that usually interact in serving different cognitive functions. On the other hand, these regions are also involved in cognitive processing of emotions but their contribution to emotional processing is not well-studied. In the present study, we investigated the role of these regions in three dimensions (valence, arousal and dominance) of emotional processing of stimuli via ratings of visual stimuli performed by the study partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 104 publications
(85 citation statements)
references
References 106 publications
3
67
0
Order By: Relevance
“…However, in the current study, tDCS applied to the prefrontal cortex did not reveal a valence specific effect. Past research has shown mixed results regarding the role of valence on tDCS effects, with some studies showing valencedependent tDCS effects (Mondino et al, 2015;Nejati et al, 2021), and others showing valence-independent tDCS effects (Sanchez-Lopez et al, 2018). Possibly, in the current study, tDCS could have promoted the employment of a general and sustained attentional strategy to a broader context of social evaluative threat, instead of trial-by-trial adjustments based on valence.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…However, in the current study, tDCS applied to the prefrontal cortex did not reveal a valence specific effect. Past research has shown mixed results regarding the role of valence on tDCS effects, with some studies showing valencedependent tDCS effects (Mondino et al, 2015;Nejati et al, 2021), and others showing valence-independent tDCS effects (Sanchez-Lopez et al, 2018). Possibly, in the current study, tDCS could have promoted the employment of a general and sustained attentional strategy to a broader context of social evaluative threat, instead of trial-by-trial adjustments based on valence.…”
Section: Discussionmentioning
confidence: 59%
“…First, based on the self-regulation theories proposing adaptive SET reactivity consists of both decreased self-attention and increased otherattention (Hess and Pickett, 2010;Durlik and Tsakiris, 2015), and given the wide array of research showing adaptive left prefrontal tDCS effects on attention processes and emotional reactivity (Mondino et al, 2015;Smits et al, 2020), we expected that active (in contrast to sham) left prefrontal tDCS would be associated with attenuated self-attention (i.e., slower first fixation to and less total fixation time on this information) and increased other-attention (i.e., faster first fixation to and more total fixation time on this information). We had no clear expectations whether these effects would be modulated by valence, as previous prefrontal tDCS research has shown both valence-independent (Sanchez-Lopez et al, 2018;Allaert et al, 2020), and valence-dependent tDCS effects (Mondino et al, 2015;Nejati et al, 2021). Second, based on the proposed association between prefrontal-mediated attentional processes and emotional reactivity, we expected the attentional processes that are modulated by tDCS to be more strongly associated with attenuated emotional reactivity (assessed via SCRs) among participants receiving active (versus sham) tDCS.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…First, although both vmPFC and r‐TPJ are involved in social cognition, they differ in specific functions. The vmPFC is engaged in a broad range of social‐processing tasks, involving other‐ and self‐referential processing (Northoff & Bermpohl, 2004; Salehinejad, Nejati, & Nitsche, 2020; Spreng & Andrews‐Hanna, 2015) as well as emotional processing (Nejati et al, 2021; Winecoff et al, 2013), while the r‐TPJ is suggested to play a particular role in reflecting on the beliefs of other people (Spreng & Andrews‐Hanna, 2015). These broader functions of the vmPFC and medial prefrontal regions might explain the discernable effects of stimulation of the respective regions.…”
Section: Discussionmentioning
confidence: 99%
“…They found a frontoparietal network and a left-lateralized prefrontal network, linked mainly to the cognition domain [25]. Previous studies have shown that despite memory decline, the executive function is also impaired in aMCI [26,27], which may affect the efficiency and time course of emotion regulation. Combined with these results, the effectiveness of downregulating emotions will evidently be influenced by cognitive decline, but this influence has not yet been systematically tested.…”
Section: Introductionmentioning
confidence: 95%